PENGARUH IRADIASI SINAR GAMMA [60Co] TERHADAP BACTROCERA CARAMBOLAE DREW & HANCOCK IN VITRO DAN IN VIVO - Endang Sri Ratna; Kemas Usman; Indah Arastuti; Dadan Hindayana (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Effect of gamma irradiation [60Co] against Bactrocera carambolae Drew & Hancock in vitro and in vivo. Bactrocera carambolae Drew & Hancock is one of the most important pests on guava fruit. According to a quarantine regulation in export-import commodities, irradiation treatment is a suitable methods for eradicating infested organism, which is relatively safe for the environment. The aim of this research was to determine mortality doses and an effective dose of [60Co] gamma ray irradiation for the eradication purpose, and its implication on the survival of fruit fly B. carambolae. Two irradiation methods of in vitro dan in vivo were carried out, by exposing egg and 3rd instar larvae of B. carambolae obtained from the laboratory reared insect. Eleven doses of gamma ray irradiation of 0, 30, 50, 75, 100, 125, 150, 175, 200, 300, 450, and 600 Gy were applied, respectively. The level of 99% fruit fly mortality was estimated by the value of LD99 using probit analysis and the number of larvae, pupae and adult survival were evaluated by analysis of variance (ANOVA), and the means compared by Tukey’s test, at 5% of significance level. These result showed that the effective lethal dose (LD99) of irradiation that could be successful to eradicate eggs and 3rd instar larvae in vitro were 2225 and 2343 Gy and in vivo were 3165 dan 3177 Gy, respectively. Almost all of the treated larvae survived and developed to pupae, therefore only the minimum irradiation dose of 30 Gy allowed the pupae to develop into adults.